Corrosion Resistance of SiO2 Aerogel Loaded with Benzotriazole Inhibitor in K2SiO3 Coatings - HAO Guoqiang, WANG Shuchuang, CHEN Zengyong, ZHANG Xinyi, LIU Xianwen, WANG Shirong, YANG Jingxia (Cailiao Baohu)
In order to enhance the corrosion protection of K2SiO3 coatings， SiO2 aerogel (SA) was used as a carrier loaded with 70 mg/mL benzotriazole (BTA) corrosion inhibitor (SA＠BTA-70).The SA＠BTA-70 dispersion and BTA slow-release properties in K2SiO3 solution were researched，and their influence on the corrosion resistance of K2SiO3 coatings were also investigated.Moreover，the surface change of SiO2 aerogel before and after heat treatment at 600 ℃was investigated by Fourier transform infrared spectrometer， specific surface area adsorption tester， etc.to improve its dispersibility in aqueous K2SiO3.Through TGA and UV-vis monitoring，it was found that the effective load of BTA in SiO2 aerogel was 17.6%(mass fraction)， and it had good slow-release performance under weak acidic / alkaline condition.Electrochemical impedance spectroscopy (EIS) results showed the low-frequency impedance of the K2SiO3 coating containing SA＠BTA-70 was around 5.0 ×103 Ω·cm2.The neutral salt spray resistance test showed that no obvious rust spots appeared after salt spray resistance test for 30 d， demonstrating the coating possessed excellent corrosion protection ability.From the above results， it could be obtained that SiO2 aerogel effectively loaded BTA corrosion inhibitor， and had good slow release in K2SiO3 solution， which effectively improved the corrosion resistance of K2SiO3 coatings.